Competition between Ag+ and Ni2+ in nickel enzymes: Implications for the Ag+ antibacterial activity. (December 2022) - Dobrev, Stefan; Kircheva, Nikoleta; Nikolova, Valya; Angelova, Silvia; Dudev, Todor
Abstract: Silver's antimicrobial properties have been known for centuries, but exactly how it kills bacteria is still a mystery. Information on the competition between the native Ni 2+ and abiogenic Ag + cations in bacterial systems is also critically lacking. For example, urease, a famous nickel-containing enzyme that hydrolyzes urea into carbon dioxide and ammonia (a key step in the biogeochemical nitrogen cycle on Earth), is inhibited by Ag + cations, but the molecular mechanism of silver's action is poorly understood. By employing density functional theory (DFT) calculations combined with the polarizable continuum model (PCM) computations we assess the susceptibility of the mono/binuclear Ni 2+ binding sites in the nickel enzymatic centers to Ni 2+ →Ag + substitution. The active centers in the mononuclear glyoxalase I and acireductone dioxygenase enzymes appear to be well protected against Ag + attack and, presumably, stay functional even in its presence. On the other hand, the binuclear nickel binding site in urease appears vulnerable to silver attack - the results obtained are in line with available experimental data and give reason to assume a possible substitution of the essential Ni 2+ cation from the urease metal center by Ag + . Graphical Abstract: Information on the competition between the native Ni 2+ and abiogenic Ag + cations in bacterial systems is critically lacking. By employing DFT-PCM calculations we assess the susceptibility of the mono/binuclear Ni 2+ binding sites in the nickel enzymatic centers of glyoxalase I, acireductone dioxygenase and urease to Ni 2+ →Ag + substitution. ga1 Highlights: Factors controlling Ag + /Ni 2+ competition in bacterial metalloproteins are elucidated. Mononuclear Ni 2+ binding sites appear protected against the attacks from Ag + . Charged or highly polarizable ligands boost the Ni 2+ /Ag + competitiveness. Reduced solvent exposure of the binding pocket is beneficial for Ni 2+ →Ag + exchange. Binuclear Ni 2+ binding site in urease appears vulnerable to silver attack.